1997
DOI: 10.1079/bjn19970026
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between micronutrient intake and biochemical indicators of nutrient adequacy in a ‘free-living’ elderly UK population

Abstract: Nutritional assessments are frequently based on amounts of nutrients consumed. In the present paper the usefulness of nutrient intake data for assessing nutrient adequacy is examined in an elderly British population. Subjects were 'free-living' elderly aged 68-90 years (sixty men, eightyfive women) in Norwich. Forty-two of forty-nine surviving males and sixty-seven of seventy-nine surviving females were reassessed after 2 years. With few exceptions, estimated micronutrient intake was not statistically predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
2
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 18 publications
10
44
2
2
Order By: Relevance
“…These data suggest a low prevalence of Zn deficiency in free-living ageing European people. This low prevalence of Zn deficiency in a free-living elderly population confirms previous data from others studies which report prevalence at 5% in a study in Boston and 3-4% in EuronutSeneca European-based study (Bailey et al, 1997), but are very different from data reported in hospitalised elderly, in which 28% (Pepersack et al, 2001) or 38% had plasma Zn below the cutoff value of deficiency (Schmuck et al, 1996).…”
Section: Discussionsupporting
confidence: 80%
“…These data suggest a low prevalence of Zn deficiency in free-living ageing European people. This low prevalence of Zn deficiency in a free-living elderly population confirms previous data from others studies which report prevalence at 5% in a study in Boston and 3-4% in EuronutSeneca European-based study (Bailey et al, 1997), but are very different from data reported in hospitalised elderly, in which 28% (Pepersack et al, 2001) or 38% had plasma Zn below the cutoff value of deficiency (Schmuck et al, 1996).…”
Section: Discussionsupporting
confidence: 80%
“…This paradox has also been noted in other recent studies of older people in the UK (Bailey et al 1997;Madigan et al 1998). Table 3 lists mean values for the biochemical status indices where there were significant differences between free-living participants and those in institutions, and examines the percentage differences between these two population groups, adjusted for age (since there was a highly significant difference in age profile between the two groups) and for sex.…”
Section: Biochemical Status Indicesmentioning
confidence: 82%
“…Diversos estudios nacionales 19,30,31 , regionales 13,15 , otros países en vías de desarrollo 27 e incluso de países desarrollados 26,28,32,33 han mostrado una ingesta inadecuada de zinc en los adultos mayores, acentuándose la reducción de la ingesta con la edad 5 . Por otra parte, una ingesta insufi ciente de cobre en este grupo etario ha sido demostrada en estudios nacionales 19,29 y algunos realizados en países desarrollados 32,34 . En una muestra representativa de la población de Santiago, Chile, encontramos en adultos mayores de 60 años que 86,4% de los hombres y 57,9% de las mujeres tenía una ingesta de zinc menor al requerimiento promedio estimado de zinc, siendo esta frecuencia para el cobre de 7,7% en hombres y 21,1% en mujeres 19 .…”
Section: Prevalencia De Deficiencia De Zn Y Cu En Adultos Mayores -Munclassified